PVP coated copper–iron oxide nanocomposite as an efficient catalyst for Click reactions. Issue 28 (8th July 2015) - Joshi, Neha; Banerjee, Shaibal
Graphical abstract: Abstract: A highly efficient Polyvinylpyrrolidone (PVP) coated copper–iron oxide magnetic nanoparticles as catalyst has been developed for the Huisgen 1, 3-dipolar cycloaddition reactions between organic azides and terminal alkynes which is known to be the best example in click chemistry. The in situ generated Cu(I) species is the catalytically active species for click reaction. Wide ranges of 1, 2, 3 triazoles have been synthesized in good yields by use of the catalyst at room temperature. This nanocatalyst can be recovered by applying an external magnetic field which results in easy separation of the catalyst without filtration and can be reused three times without loss of its significant activity. This catalyst was characterized by FT-IR, XRD, XPS, FESEM, and TEM.